2021
DOI: 10.1016/j.reth.2021.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adipose tissue-derived stromal cells of mice with nonalcoholic fatty liver disease and their use for liver repair

Abstract: Introduction Freshly isolated uncultured adipose tissue-derived stromal cells (u-ADSCs), containing miscellaneous cells like the relatively abundant mesenchymal stem cells, are attractive for repair and regenerative therapy. However, the detailed characteristics and therapeutic efficacy of u-ADSCs obtained from disease-affected hosts are unknown. We compared the properties of u-ADSCs obtained from wild-type mice and from a mouse model of non-alcoholic steatohepatitis (NASH). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…This is mediated by triggering Notch signaling [71]. Based on the above study, Yano et al [72] transplanted ADSCs into NASH-related cirrhotic mice and observed decreased infiltration of inflammatory cytokines (CD11b+, Gr-1+, etc. ), improved liver fibrogenesis, and repaired damaged liver tissue.…”
Section: Immunomodulatory Effect Of Mscsmentioning
confidence: 94%
“…This is mediated by triggering Notch signaling [71]. Based on the above study, Yano et al [72] transplanted ADSCs into NASH-related cirrhotic mice and observed decreased infiltration of inflammatory cytokines (CD11b+, Gr-1+, etc. ), improved liver fibrogenesis, and repaired damaged liver tissue.…”
Section: Immunomodulatory Effect Of Mscsmentioning
confidence: 94%
“…Another discovery was that MSC transplantation inhibited NASH progression by reducing hepatic inflammation, as demonstrated by the decreased expression of the acute-phase protein serum amyloid A, inflammation-associated markers such as lipocalin 2, and the proinflammatory cytokine TNF-α[ 54 , 55 ]. The ability of ADSCs to hinder NASH progression by mitigating IL-17-mediated and other inflammatory effects underscores their therapeutic potential, showing outcomes comparable to those of both NASH-specific uncultured adipose tissue-derived stromal cells (u-ADSCs) and wild-type u-ADSCs[ 56 , 57 ]. An integrated approach, employing either a combination of MSCs and MSC-EVs or solely MSC-EVs led to a noticeable increase in the number of anti-inflammatory macrophages in the liver, showing their robust immunomodulatory potency in NASH[ 45 , 49 , 58 ].…”
Section: The Roles Of Mscs In Treating Nafld/nashmentioning
confidence: 99%
“…In certain studies, ADSC treatments have been shown to effectively inhibit the progression of NASH fibrosis by targeting IL-17-mediated inflammation, a key factor in the activation of hepatic stellate cells (HSCs)[ 57 ]. Interestingly, both NASH-derived u-ADSCs and wild-type u-ADSCs show promise in preventing and reducing fibrosis in NASH[ 56 ].…”
Section: The Roles Of Mscs In Treating Nafld/nashmentioning
confidence: 99%
“…Based on these advantages, ASCs are being investigated as a therapeutic strategy for various pathological conditions, including hard-to-heal wounds. Currently, ASCs are employed in many early clinical trials for inflammatory and autoimmune diseases, ischemic heart disease, limb ischemia, fistulas, liver disease, and orthopedics, where their safety and efficiency have been verified and revealed great promise [28][29][30][31][32][33][34][35]. Cutaneous wounds treated with ASCs have exhibited great therapeutic potential [36][37][38].…”
Section: Adipose-derived Stem Cellsmentioning
confidence: 99%